2018
DOI: 10.1038/s41593-017-0061-5
|View full text |Cite
|
Sign up to set email alerts
|

Dentate network activity is necessary for spatial working memory by supporting CA3 sharp-wave ripple generation and prospective firing of CA3 neurons

Abstract: Complex spatial working memory (WM) tasks have been shown to require both hippocampal sharp wave ripple (SWR) activity and dentate gyrus (DG) neuronal activity. We therefore asked whether DG inputs to CA3 contribute to spatial WM by promoting SWR generation. Recordings from DG and CA3 while rats performed a dentate-dependent WM task on an 8-arm radial maze revealed that the activity of dentate neurons and the incidence rate of SWRs both increased during reward consumption. We then found reduced reward-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
117
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 117 publications
(143 citation statements)
references
References 56 publications
12
117
0
Order By: Relevance
“…There are multiple potential candidates that may account for input asymmetry. The dentate gyrus (Sasaki et al, 2018;Sullivan et al, 2011), CA2 (Oliva et al, 2016a), and GABAergic projections from the medial septum (Dragoi et al, 1999;Viney et al, 2013) have been implicated in sharp-wave ripple initiation. Paucity of data about the projection patterns of these regions onto CA1 restricts our ability to understand their possible role in our observations.…”
Section: Discussionmentioning
confidence: 99%
“…There are multiple potential candidates that may account for input asymmetry. The dentate gyrus (Sasaki et al, 2018;Sullivan et al, 2011), CA2 (Oliva et al, 2016a), and GABAergic projections from the medial septum (Dragoi et al, 1999;Viney et al, 2013) have been implicated in sharp-wave ripple initiation. Paucity of data about the projection patterns of these regions onto CA1 restricts our ability to understand their possible role in our observations.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous electrophysiological studies have revealed that hippocampal neurons encode sequences of spatial locations [15]. Both hippocampal pyramidal and granule neurons encode prospective information as rats plan future navigational behaviors [48][49][50][51]. Adult neurogenesis may therefore be involved in navigational planning, which is supported by recent evidence that new neurons promote choice of advantageous, but delayed, rewards.…”
Section: Adult Neurogenesis Promotes a Sequential Search Strategymentioning
confidence: 94%
“…A recent model has addressed how fast, rhythmic gamma-frequency feedback inhibition may implement a type of 'k-winners-take-all' operation, a basic computational component of pattern separation models 60 , though this model relies on faster synaptic timescales than we observed in our compound IPSCs. Perhaps most interestingly, the occurrence of oscillations in the slow-gamma range has recently been reported to be causally related to associative memory formation 41,44 , a process thought to require pattern separation. Consistent with this finding, Hsiao et al 43 report DG driven gamma entrainment of CA3, the presumed primary storage location of associative memories.…”
Section: Frequency-dependent Effects Of Feedback Inhibition On Pattermentioning
confidence: 99%
“…It is furthermore necessary to quantify the spatial and temporal properties of the elicited inhibition, in order to investigate its impact on biologically plausible, temporally structured input. For instance, the DG shows prominent theta oscillations during exploration and distinctive slow-gamma activity during associative memory encoding [41][42][43][44] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation